NILAI AGAMA DAN BUDAYA DALAM PANTUN NIKAH KAHWIN MASYARAKAT MELAYU BENGKALIS - Azmi, Ulul (Jurnal Ilmu Budaya, 2014)
The values of faith and worship are inseparable elements in the life of Bengkalis society. This is reflected in the life of the individual since his/ her childhood to his/her adulthood. These values are also portrayed in “Pantun Nikah Kawin” in which it provides advices for the new wedded couple in order they may get happiness in their life. Those advice are taken from Islamic guidance to guide the life.